Morphological Changes in Productive and Abortive Infection by Feline Herpesvirus - Abraham, Andrew (1970)
Feline herpesvirus produces characteristic morphological alterations in feline kidney cells. Nucleocapsid particles are formed in infected nuclei and are enveloped as they pass through the modified inner nuclear membrane. Aggregates of dense granular material and filamentous structures also regularly appear in infected nuclei. Infection of human embryonic lung cells by feline herpesvirus results in the appearance of intranuclear inclusion bodies, aggregates of dense granular material, and bundles of parallel filaments but no nucleocapsid particles.